(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article deals with the solution of the scientific problem to find methodological approaches to substantiation of the analytical model of parameters of the Vacuum Pump filter. As a result of the research, the equation for determining the velocity of motion of the oil particle when it removes from a vacuum pump and enter the filter of the muffler, the latter has a step increase in the radius and an expression for its determination. The author takes into account that the mass of the particle is not directly included in the formula for the air pressure. However, the mass affects the acceleration of the particle under the influence of pressure. If the air pressure exceeds gravity, the proportion will accelerate. The author considers, in terms of the process that occurs in the filter, it should be noted that the increase in the speed of movement of olive particles should lead to improving the purification effect, as centrifugal forces that act on the particles increase.